2020
DOI: 10.1007/s00330-020-06778-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of machine-learning CT-derived fractional flow reserve for the diagnosis and management of coronary artery disease in the randomized CRESCENT trials

Abstract: Objective To determine the potential impact of on-site CT-derived fractional flow reserve (CT-FFR) on the diagnostic efficiency and effectiveness of coronary CT angiography (CCTA) in patients with obstructive coronary artery disease (CAD) on CCTA. Methods This observational cohort study included patients with suspected CAD who had been randomized to cardiac CT in the CRESCENT I and II trials. On-site CT-FFR was blindly performed in all patients with at least one ≥ 50% stenosis on CCTA and no exclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…If the above diagnostic strategy had been applied to the current cohort, dynamic CT-MPI could have been avoided in 33.9% of patients while maintaining uncompromised diagnostic accuracy, leading to a 27.0% and 33.9% reduction in radiation dose and contrast medium usage, respectively. Furthermore, previous studies have demonstrated that CT-FFR may improve downstream clinical management in patients with an intermediateto-high pretest probability of CAD (29,30). The current findings also confirmed the value of CT-FFR in guiding clinical decisions, especially when integrated with dynamic CT-MPI.…”
Section: Discussionmentioning
confidence: 99%
“…If the above diagnostic strategy had been applied to the current cohort, dynamic CT-MPI could have been avoided in 33.9% of patients while maintaining uncompromised diagnostic accuracy, leading to a 27.0% and 33.9% reduction in radiation dose and contrast medium usage, respectively. Furthermore, previous studies have demonstrated that CT-FFR may improve downstream clinical management in patients with an intermediateto-high pretest probability of CAD (29,30). The current findings also confirmed the value of CT-FFR in guiding clinical decisions, especially when integrated with dynamic CT-MPI.…”
Section: Discussionmentioning
confidence: 99%
“…FFR is based on a proportional linear relationship between coronary blood flow and perfusion pressure during maximal vasodilation [55] and has been widely validated [30]. However, its cost, availability, vasodilator need [10,61], and poor hemodynamic correlation [50,66] makes its use for physiological assessment meet the current guideline indicators in only 50% of the cases [19]. FFR importance is questioned [66] as well as hyperemia is suggested not to be essential to the correct diagnose [7].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…From 2018 onwards, coronary computed tomography angiography (CCTA) has also been indicated to exclude significant coronary artery diseases in patients with low-to-intermediate lesions due its sensitivity and negative predictive value [9,28,34,37,40,50]. CCTA provides geometrical characteristics such as diameter and area of the lesion and is based in visual assessment [73], but similar to CCA, it is insufficient to provide lesion hemodynamic information [37].…”
Section: Conducting the Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…However, CCTA generates exclusively morphological information about coronary arteries. To diagnose the presence of myocardial ischemia irrespective of the presence coronary artery stenosis, it is recommended that myocardial perfusion should be assessed with another modality [8][9][10]. Studies that have detected myocardial ischemia by diagnostic imaging on stable angina primarily use sensitivity and speci city as indices, thus indicating their ability.…”
Section: Introductionmentioning
confidence: 99%